A New Total Wrist Fusion Locking Plate for Patients with Small Hands or with Failed Partial Wrist Fusion: Preliminary Experience - del Pino, Juan González (Journal of Wrist Surgery, 2014)
The author has designed a custom-made titanium plate for total wrist fusion for small-handed persons or patients with failed partial wrist fusions. From May 2011 to April 2013, this plate was used on 13 wrists, 5 of them with a minimum follow-up of 1 year. This implant is downsized compared with the standard wrist fusion plate: lower in profile, shorter in length, and narrower than the standard one. It is fixed to the radius by means of 2.7-mm screws and to the capitate and third metacarpal with 2.4-mm screws. In the curved plate all the screws are locked to the plate with a predetermined coaxial angle. The plate has a curvature to fit the dorsum of the carpus; it is 10° dorsally extended and has undercuts on the contact areas at the radius and third metacarpal dorsal surface. The indication for this implant is a short-statured patient for whom the standard plate is too large and bulky; a failed partial wrist fusion or proximal row carpectomy, for which a shorter plate is needed because only one articulation should be fused (midcarpal or radiocapitate joint); or both. The five wrists (two primary fusions and three failed radioscapholunate [RSL] fusions) healed between 11 and 14 weeks. No plate loosening was observed, and none of the patients felt painful prominence to the distal end of the plate on the dorsum of the hand.
Keywords: wrist; total wrist fusion; partial wrist fusion; locking plate